ГНУЧКЕ КЕРУВАННЯ ЕКСПОРТНИМИ ПЕРЕТОКАМИ З ВИКОРИСТАННЯМ ВСТАВКИ ПОСТІЙНОГО СТРУМУ - Кириленко, О.В.; Павловський, В.В.; Стелюк, А.О. (Інститут електродинаміки НАН України, Київ, 2015)
The functional possibilities of modern direct current (DC) links for a power system control have been considered. The organization structure of the load frequency control in the interconnected power system of Ukraine is proposed in case of DC link construction near Khmelnitskaya nuclear power plant. The simulation results are shown in the event of the generating unit disconnection at Burshtyn thermal power plant. It is established that DC link connection to the active power controller of “Burshtyn island” allows providing the flexible control of the export power flows in alternating and direct current networks. References 10, table 1, figures 5.